Practical aspects of using HRTF measuring device - Plaskota, Przemysław; Pruchnicki, P. (Archives of Acoustics, 2006)
Measurement of Head Related Transfer Function is complicated due to the object of thetest, namely the transfer function of acoustical arrangement composed of pinna, head andtorso. The test involving the participation of a person requires providing appropriate conditionsfor conducting measurement. Maintaining constant geometrical configuration of thesound source and the microphone placed in the ear’s channel is particularly important. Fulfillingthis condition as well as determining the exact position of the sound source in relationto the measurement microphone may require application of a special measurement device.The paper presents the results of measuring HRTF function using special device. The problemsencountered during the measuring process are discussed and the possible solutions aresuggested. Finally, the results of the tests for a real human subject are presented in the paper.